A Socialist Approach to Translation: A Way Forward? - Thomson-Wohlgemuth, Gabriele (Meta, 2004)
AbstractWithin the German Democratic Republic (GDR) during the period of the Cold War, a new approach was created to the processes involved in literary translation, in fact the whole publishing industry was reorganised. Recognising translation as a social practice, the GDR consciously established conditions which encompassed the whole working environment with the aim of producing high quality translations. By recognising the historical significance of this approach, it may be abstracted and adapted to contemporary society. In so doing, it is believed that it can be developed into a constructive addition to the field of Translation Studies today.